Multi-centered clinical validation demonstrating superior precision in lupus diagnosis: T cell autoantibodies and TC4d outperform conventional lupus erythematosus biomarkers - Kyttaris, Vasileios; Wallace, Daniel J.; Khosroshahi, Arezou; Concoff, Andrew; Wilson, Nicole; Liu, Chau Ching; Manzi, Susan; Ahearn, Joseph; Taghavi, Sepehr; Warsi, Touba; Park, Stanley; Schleif, Christine; et al. (Frontiers in Immunology, 2025)
IntroductionT Cell autoantibodies, TIgG and TIgM, as well as the T Cell-bound complement protein fragment C4d (TC4d) are novel diagnostic biomarkers that have demonstrated high specificity and sensitivity for SLE. The present study aims to characterize the clinical performance characteristics of the emergent T Cell biomarkers in a multi-center clinical validation cohort.MethodsA cohort of 400 adult patients enrolled across 3 academic and 2 community-based autoimmune rheumatic centers, comprised of 105 SLE patients, 173 patients with autoimmune rheumatic diseases (ARD), 83 apparently healthy volunteers (AHV) and 39 other (non-autoimmune) disease (OD) controls were tested for TC4d, TIgG, TIgM and an extensive autoantibody profile. Diagnostic specificity was assessed against the ARD, AHV and OD groups, individually. Semi-quantitative flow cytometry analysis included TIgG and TIgM autoantibodies, cell-bound complement activation products (CB-CAPs), TC4d, erythrocyte-bound C4d (EC4d) and B lymphocyte-bound C4d (BC4d). Conventional autoantibodies and soluble complement proteins, C3 and C4, were assessed by ELISA and immunoturbidimetry, respectively.ResultsROC analysis distinguishing ANA-positive (ANA+) SLE (N = 91) from ARD, TIgG, BC4d and TC4d demonstrated AUC values 0.81, 0.80 and 0.79, respectively, outperforming anti-dsDNA (0.72), C3 (0.69), TIgM (0.67), C4 (0.66) and anti-Smith (0.61). A similar ranking of discriminatory power was observed in ROC analysis distinguishing ANA+ SLE vs. OD as well as ANA+ SLE vs. AHV. At 95% diagnostic specificity for SLE vs. AHV, the sensitivity (95% CI) of TC4d, TIgG and TIgM for SLE was 58.1% (48.1 – 67.7%), 31.4% (22.7 – 41.2%) and 29.5% (21.0 – 39.2%), respectively. The T Cell SLE biomarkers uniquely identified 19% (20/105) of SLE patients who were otherwise negative (serologically inactive) for conventional SLE autoantibodies and had normal serum complement levels. Among the serologically inactive SLE subset, the T Cell SLE biomarkers collectively identified 53% of subjects.ConclusionsThe novel SLE biomarkers TC4d, TIgG and TIgM consistently outperform conventional markers across multiple cohorts. Their integration enhances diagnostic sensitivity, especially in SLE-specific autoantibody negative patients with normal complement levels. When coupled with conventional biomarkers, these novel tests may enable earlier and more accurate SLE detection, leading to more timely diagnosis and treatment.